Animation Media Based on Scratch 3.0 Software to Improve Student Understanding of Pronunciation Material at Junior High School - Rofik; Eges Triwahyuni; Hariyanto (JST (Jurnal Sains dan Teknologi), 2025)
The low ability of students in understanding pronunciation indicates that English learning still faces serious challenges. This occurs because innovative learning media have not been applied optimally, resulting in conventional and less interactive teaching. This study aims to develop and test the effectiveness of Scratch 3.0 as a learning medium in improving students’ pronunciation comprehension by analyzing, evaluating, and validating the media comprehensively. The type of research used is development research with the ADDIE model. The research subjects consist of two trial groups: an experimental class with 30 students and a comparison group with 32 students. Research data were collected through media expert validation, material expert validation, student response questionnaires, as well as learning achievement tests in the form of pretests and posttests. The research instruments included validation sheets, questionnaires, and test items to ensure the quality and effectiveness of the media. Data analysis was conducted using descriptive quantitative methods through validity tests, feasibility assessments, and calculations of students’ learning improvement. The results of the study show that Scratch 3.0 is proven to be valid, feasible, and effective in significantly improving students’ pronunciation comprehension. Thus, it can be concluded that the development of this media successfully addresses the problem of students’ low understanding of pronunciation. The implication of this research is that Scratch 3.0 can be used as an alternative innovative learning medium that encourages students to be more active, independent, and motivated in learning English.